Trade advantages and specialisation dynamics in acceding countries - Andrea Zaghini (European Central Bank (ECB), 2003)
The paper analyses the evolution of the trade specialisation pattern in the ten countries which will join the EU in 2004, by studying the dynamics of their comparative advantages over the period 1993-2000. The study finds that, although some countries are still broadly relying on natural resources, most of them enjoy significant comparative advantages in many manufactured goods. Moreover, in spite of large technological gaps inherited from the long period of centrally planned economy, some were able to specialise in "high tech" products. Finally, most countries recorded large specialisation improvements in items for which the world demand expanded at the fastest rate over the Nineties; in particular, Estonia, Hungary, Malta and Slovenia showed an overall positive comparative advantage in the set of the most demanded products.
Keywords: F14; F15; E23; 330; Distribution dynamics; International Specialisation model; Revealed comparative advantages